Gold Is Once Again Becoming The World's Favorite Reserve Asset: The Dynamics of De-dollarization - Dian Eka Wahyuni; Rintan Dwi Aprilian; Bintang Lazuardi Benteng Buana Muslim (Journal of Innovation, Business Management and Entrepreneurship, 2025)
The acceleration of the trend toward de-dollarization reflects structural transformation in the global financial architecture. This study aims to analyze the main drivers of this phenomenon and the strategic role of gold, which has once again become the preferred global reserve asset. Using a descriptive qualitative approach with secondary data from the World Gold Council and the IMF (2010-2024 period), this study identifies three key factors: geopolitics (financial sanctions and rivalry between major powers), economics (US fiscal deficits and inflation), and structural factors (BRICS efforts to establish a non-dollar payment system). The results show that gold has been repositioned as a strategic “shield” against the risks of sanctions and monetary uncertainty, rather than merely an investment commodity. In conclusion, the aggressive accumulation of gold by central banks signals a shift towards a multipolar order, where economic stability and sovereignty take precedence over the efficiency of the dollar-based system.